National trends in psychotropic medication use in young children: 1994-2009 - Vilawan Chirdkiatgumchai (2018)
Objective: To examine recent national trends in psychotropic use for very young children at US outpatient medical visits. Methods: Data for 2- to 5-year-old children (N = 43 598) from the 1994-2009 National Ambulatory and National Hospital Ambulatory Medical Care Surveys were used to estimate the weighted percentage of visits with psychotropic prescriptions. Multivariable logistic regression was used to identify factors associated with psychotropic use. Time effects were examined in 4-year blocks (1994-1997, 1998-2001, 2002-2005, and 2006-2009). Results: Psychotropic prescription rates were 0.98% from 1994-1997, 0.83% from 1998-2001, 1.45% from 2002-2005, and 1.00% from 2006- 2009. The likelihood of preschool psychotropic use was highest in 2002-2005 (1994-1997 adjusted odds ratio [AOR] versus 2002-2005: 0.67; 1998-2001 AOR versus 2002-2005: 0.63; 2006-2009 AOR versus 2002-2005: 0.64), then diminished such that the 2006-2009 probability of use did not differ from 1994-1997 or from 1998-2001. Boys (AOR versus girls: 1.64), white children (AOR versus other race: 1.42), older children (AOR for 4 to 5 vs 2 to 3 year olds: 3.87), and those lacking private insurance (AOR versus privately insured: 2.38) were more likely than children from other groups to receive psychotropic prescriptions. Conclusions: Psychotropic prescription was notable for peak usage in 2002-2005 and sociodemographic disparities in use. Further study is needed to discern why psychotropic use in very young children stabilized in 2006-2009, as well as reasons for increased use in boys, white children, and those lacking private health insurance. © 2013 by the American Academy of Pediatrics.